2020
DOI: 10.1186/s12903-020-01353-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of periodontitis according to the immunological and virological profiles of HIV-infected patients in Yaoundé, Cameroon

Abstract: Background HIV infection is associated to different oral manifestations (including periodontal diseases), which have decreased with the advent of antiretroviral therapy (ART). Yet, the occurrence of periodontitis is still consistent among patients with HIV living in sub Saharan-Africa, with limited evidence on the driven factors and mitigating measures in these settings. We aimed at evaluating the occurrence of periodontitis and its associated immunological and virological factors in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…In the present study, no difference in the PISA was found between the groups with CD4+ cell counts of ≥500/mm 3 and <500/mm 3 or between the HIV detection and HIV non-detection groups. The lack of any difference in the PISA is consistent with previous reports that periodontal disease indicators such as PPD (≥4 mm) and BOP are not associated with CD4+ T-cell counts (Fokam et al, 2020;Gonçalves et al, 2005;John et al, 2013;Ravi & Rao, 2015). examination were significantly lower after the initial periodontal treatment than those at baseline.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, no difference in the PISA was found between the groups with CD4+ cell counts of ≥500/mm 3 and <500/mm 3 or between the HIV detection and HIV non-detection groups. The lack of any difference in the PISA is consistent with previous reports that periodontal disease indicators such as PPD (≥4 mm) and BOP are not associated with CD4+ T-cell counts (Fokam et al, 2020;Gonçalves et al, 2005;John et al, 2013;Ravi & Rao, 2015). examination were significantly lower after the initial periodontal treatment than those at baseline.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported that patients with HIV infection and high CD4+ T-cell counts have more advanced periodontal diseases than those with low CD4+ T-cell counts (McKaig et al, 2000;Valentine et al, 2016). Other studies have found no difference in the pathogenesis of periodontitis according to the CD4+ T-cell counts (Fokam et al, 2020;John et al, 2013). Thus, the effect of CD4+ T-cell counts on the pathogenesis of periodontitis remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, men in the aforementioned study had signi cantly higher risk of clinical attachment loss than women [4].…”
Section: Introductionmentioning
confidence: 78%
“…With the use of effective antiretroviral therapy (ART), people living with HIV (PLWH) experience life expectancies similar to people without HIV and encounter many more aging-related comorbidities [3] than opportunistic infections. A recent study con rmed the protective role of ART as the prevalence of periodontitis in PLWH not receiving ART was two times greater than those PLWH receiving ART [4].…”
Section: Introductionmentioning
confidence: 98%
“…A study done in France in 2014, reported that pseudomembranous (25%) and erythematous (13.9%) candidiasis were the most encountered forms of oral candidiasis [ 11 ]. Meanwhile, in Cameroon, a study demonstrated the presence of periodontitis in HIV-infected people in Yaoundé, with a significantly high morbidity in those with a deleterious immune status (53.2%) but without exploration of the typology [ 12 ]. In order to limit HIV related oral disease and to optimize oral healthcare among PLHIV, we evaluated the type and distribution of oral candidiasis with respect to ART-profile including both immunological and virological profiles of PLHIV in two health facilities (Chantal Biya International Reference Centre for Research on HIV/AIDS Prevention and Management (CIRCB) and the Jamot Hospital of Yaoundé); which are respectively among the leading HIV/AIDS monitoring (viral load and CD4 count) and treatment sites in Yaoundé.…”
Section: Introductionmentioning
confidence: 99%